2012
DOI: 10.1371/journal.pgen.1002896
|View full text |Cite
|
Sign up to set email alerts
|

SEMA3A, a Gene Involved in Axonal Pathfinding, Is Mutated in Patients with Kallmann Syndrome

Abstract: Kallmann syndrome (KS) associates congenital hypogonadism due to gonadotropin-releasing hormone (GnRH) deficiency and anosmia. The genetics of KS involves various modes of transmission, including oligogenic inheritance. Here, we report that Nrp1 sema/sema mutant mice that lack a functional semaphorin-binding domain in neuropilin-1, an obligatory coreceptor of semaphorin-3A, have a KS–like phenotype. Pathohistological analysis of these mice indeed showed abnormal development of the peripheral olfactory system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
211
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(231 citation statements)
references
References 33 publications
15
211
2
3
Order By: Relevance
“…Finally, a heterozygous intragenic SEMA3A deletion was recently observed in a father and his two children with signs of Kallmann syndrome (hypogonadotropic hypogonadism and anosmia) and supported by the mouse findings of Cariboni et al [2011] was considered causative . However, a study of SEMA3A mutations in 386 patients with Kallmann syndrome suggested that monoallelic mutations in SEMA3A were not sufficient to induce the abnormal phenotype, but may contribute to the pathogenesis of Kallmann syndrome through synergistic effects with mutant alleles of other disease-associated genes [Hanchate et al, 2012]. Accordingly, neither our compound heterozygous patient nor his heterozygous father had obvious signs of Kallmann syndrome.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Finally, a heterozygous intragenic SEMA3A deletion was recently observed in a father and his two children with signs of Kallmann syndrome (hypogonadotropic hypogonadism and anosmia) and supported by the mouse findings of Cariboni et al [2011] was considered causative . However, a study of SEMA3A mutations in 386 patients with Kallmann syndrome suggested that monoallelic mutations in SEMA3A were not sufficient to induce the abnormal phenotype, but may contribute to the pathogenesis of Kallmann syndrome through synergistic effects with mutant alleles of other disease-associated genes [Hanchate et al, 2012]. Accordingly, neither our compound heterozygous patient nor his heterozygous father had obvious signs of Kallmann syndrome.…”
Section: Discussionmentioning
confidence: 67%
“…Due to the pivotal role of SEMA3A in development, it was widely studied in a variety of human conditions and heterozygous variants have been associated with Hirschsprung disease [Jiang et al, 2012], with the crypt frequency in human iris patterns [Larsson et al, 2011]; and with hypogonadotropic hypogonadism and anosmia (Kallmann syndrome) [Hanchate et al, 2012;Young et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in genes such as GNRH1, GRNHR, KISS1 or KISS1R (7, 8,9,10,11,12,13,14) can impair the action (or secretion) of GnRH, resulting in normosmic CHH. In contrast, mutations in genes impacting the migration of GnRH neurons from the olfactory placode during development (ANOS1, SEMA3A, IL17RD, SOX10 and FEZF1) (15,16,17,18,19,20,21) result in KS. KAL1, recently renamed ANOS1, was the first X-linked gene implicated in CHH (15,16,22,23).…”
Section: Pathophysiology and Genetics Of Chhmentioning
confidence: 98%
“…Genes encoding fibroblast growth factor 8 (FGF8) signalling pathway proteins, [17][18][19][20][21][22] chromodomain helicase DNA-binding protein 7 (CHD7) [23][24][25][26][27] and sex determining region Y-Box 10 (SOX10) 28,29 affect the neurogenic niche in the nasal area and craniofacial development. Conversely, Kallmann syndrome protein, which is now officially known as anosmin 1 (encoded by KAL1; following nomenclature change, the gene is now denoted as ANOS1), 2 prokineticin-2 and prokineticin receptor 2 (encoded by PROK2 and PROKR2, respectively), [30][31][32][33] WD repeat domain 11 (encoded by WDR11), 34,35 semaphorin 3A (encoded by SEMA3A) [36][37][38] and FEZ family zinc finger 1 (encoded by FEZF1) 39 influence migration of GnRH neurons.…”
Section: Biology Of the Gnrh Neuronal Systemmentioning
confidence: 99%
“…117,118 To date, >25 different genes have been implicated in Kallmann syndrome and/or CHH, which accounts for ~50% of cases. 21 Causative genes for Kallmann syndrome include: KAL1 (ANOS1) in the X-linked form; FGFR1 (encoding fibroblast growth factor receptor 1), 17,18 FGF8, 19,119 CHD7, [23][24][25][26][27] HS6ST1 (encoding heparan-sulphate 6-O-sulphotransferase 1), 20 SOX10, 28,29 SEMA3A (encoding semaphorin-3A), [36][37][38] WDR11 (encoding WD repeat-containing protein 11) 34,35 and IL17RD (encoding interleukin-17 receptor D) 21 in the autosomal dominant form; and PROKR2 and/or PROK2, [30][31][32][33] and FEZF1 39 in the autosomal recessive form, even though it should be noted that most patients carrying mutations in PROKR2 or PROK2 carry these mutations in the heterozygous state. 120,121 Genes involved in CHH that are associated with a normal sense of smell include GNRHR (encoding gonadotropinreleasing hormone receptor), 122,123 GNRH1 (encoding gonadotropin-releasing hormone 1), 124,125 KISS1R, 41,42 KISS1, 40,126 TACR3 and TAC3.…”
Section: Genetics Of Chhmentioning
confidence: 99%